Subjetividades de mujeres de sectores populares en la CDMX que se desempeñan en ocupaciones "masculinas" - Herrera, Cristina (El Colegio de México, 2018)
This note presents results of a study developed in Mexico City with women from popular sectors in jobs considered male and female occupations. 109 women participated in discussion groups and in-depth interviews. The analysis shows clues to a de-genderization of family and couple relationships, which becomes possible when social and cultural changes lead to a blurring of the boundaries between the masculine and feminine worlds that sustain the sexual division of labor. There is a tension between the desire for greater gender equality and the resistance to accept it. All women reproduce the discourse of the egalitarian couple as utopia, but maintain the differentiated model, both by identification and by strategy, before the risks of consumerist individualism that they perceive in their environment and that especially threatens their children.